2000
DOI: 10.1002/(sici)1521-3803(20000301)44:2<89::aid-food89>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of chemical and enzymatic hydrolysates of β-lactoglobulin: characterization of the peptides adsorbed at the interface

Abstract: Bovine beta-Lactoglobulin (BLG) was cleaved by BNPS-skatole (2-(2'-nitrophenylsulfenyl)-3-methyl-3'-bromoindolenine), trypsin, or pepsin in 40% ethanol before emulsification with hexadecane in order to characterize the peptides active at the interfaces. The total digests and the different phases obtained after emulsification were analyzed by RP-HPLC to separate the peptides according to their gradual order on a hydrophilicity-to-hydrophobicity scale. In each case, hydrophobic peptides were recovered in the cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Thus, poorer stability of CBH‐stabilised emulsion compared to RBH could be due to the smaller size peptides as well as the type of peptides produced. It should be noted, however, that other studies have reported that specific peptides rather than the molecular weight distribution play an important role in emulsifying activity and emulsion stability (Rahali et al ., ). In addition to protein and peptides, the presence of phenolic compounds could play a role in emulsion formation and stability.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, poorer stability of CBH‐stabilised emulsion compared to RBH could be due to the smaller size peptides as well as the type of peptides produced. It should be noted, however, that other studies have reported that specific peptides rather than the molecular weight distribution play an important role in emulsifying activity and emulsion stability (Rahali et al ., ). In addition to protein and peptides, the presence of phenolic compounds could play a role in emulsion formation and stability.…”
Section: Resultsmentioning
confidence: 97%
“…The EAI of both HA and HP decreased with increasing DH. According to Rahali et al ,40 in order to exhibit good emulsifying activity, the protein and/or peptides must be able to migrate rapidly to the water/oil interface and then unfold and rearrange rapidly at the interface. Additionally, although the peptides with low molecular weight can migrate rapidly to the interface, the hydrophobic/hydrophilic balance of these small peptides is not good enough to exhibit good emulsifying activity.…”
Section: Resultsmentioning
confidence: 99%
“…As the molecular sizes of the soluble proteins decreased, it was clear that also the protein structure was modified by the fermentation process, which in turn led to changes in techno-functional properties. Rahali et al [40] and Razali et al [41] reported that the surface hydrophobicity of the proteins is more important than the peptide length in emulsion and foaming properties. Most often, high surface hydrophobicity is needed to allow the formation of stable emulsions and foams.…”
Section: Quantification Of Free Amino Groups and Protein Molecular Wementioning
confidence: 99%